Proyecto de factibilidad para la creación de una microempresa productora de aceite de sacha inchi y su comercialización en el cantón Limón Indanza, provincia de Morona Santiago para el año 2016. - Vega Vega, Alexandra Ximena (2017)
The present titling work: Feasibility Project for the Creation of a Sacha Inchi Oil Production Microenterprise and its commercialization in the canton of Limón Indanza, Province of Morona Santiago, has been developed with the objective of establishing the economic and financial feasibility of The industrialization of a high quality nutritional and medicinal oil extracted from sacha inchi. In order to give guidance to the research, it was necessary to propose a general objective that would be the same: To carry out a feasibility project for the creation of a microenterprise producing sacha inchi oil and its commercialization in the canton of Limón Indanza, Morona Santiago province for the Year 2017. Also for the accomplishment are drawn specific objectives that in summary try to develop the following studies: market, technical, administrative, economic-financial, financial evaluation and evaluation of social and environmental impact. In order to meet the stated objectives, different methods and techniques were used; Among the former can be noted the methods: deductive, inductive, analytical, synthetic, mathematical and statistical; Among the techniques, the survey was used, which was applied to a representative sample of the population of the canton Limón Indanza, which was calculated in 330 surveys. For the above, the following results were obtained: 97% of the respondents consume edible oil, 88% consume sacha inchi oil, 93% if they would be willing to buy the product of the new company, with these percentages determined, The real and effective power demand, the latter is multiplied by the per capita consumption that was calculated in 36 units, and an effective demand is obtained in units of 45,156, which related to the projected supply leads to an unmet demand of 43,998 500 ml units. In the first year of the project with installed capacity is intended to cover 90.42% of unsatisfied demand, of which capacity will be used 95% in all years, ie will produce 37,620 units of 500 ml. For the execution of this project, an investment of USD 74,826.99 is required; Which will be financed, 47.71 with external sources and 52.29% with contributions from partners. The total cost for the first year is USD 62,872.52; A unit cost of USD 1.67 is established which, with a profit margin of 48%, establishes the P.V.P of USD 2.47 in the first year, which allows to have an income of USD 93.051,33. In the financial evaluation, having a positive cash flow in all the project life years, a NPV of USD 8,350.70 is determined; The IRR is 16.09%; The cost-benefit ratio is USD 1.57; The capital recovery period of 3 years, 9 months and 4 days, the sensitivity is set at 0.99 in both cost increase and decrease of income. The research work is concluded, affirming the feasibility of the project, since all the financial indicators are favorable, ie a NPV of more than 1, the IRR, is higher than the opportunity cost in the R / C for each Dollar invested, you get 57 cents of profit, the recovery period of the investment is much lower than the useful life of the project and finally you get a sensitivity lower than 1, with a cost increase of 21.18% and A decline in revenues of 13.54%